Dear Scarlett - Hitchcock, Fleur (Nosy Crow, 2013)
A funny, moving and absorbing story about a young girl's attempts to learn more about her dead father through the objects she finds in a cardboard box he's left her. Scarlett and her friend, Ellie, go on a sometimes hilarious, sometimes scary, journey of discovery, following the clues and always remembering to 'keep looking up'. Was Scarlett's dad a thief? Was he a spy? And what does it mean to be his daughter?